The role of free-radical processes in the pathogenesis of age-related macular degeneration. Review - A. V. Kolesnikov; A. V. Shchulkin; O. I. Barenina (Oftalʹmologiâ)
the modern ideas of the role of free radical processes in the pathogenesis of age-related macular degeneration (AMD) are consid- ered. Data of large randomized clinical trials on application of antioxidants for prevention and therapy AMD are provided. Possibility of the differential application of antioxidants depending on the genetic status of patients is discussed.